PENERIMAAN / SIKAP GURU DAN SISWA REGULER TERHADAP KEBERADAAN ABK SECARA FISIK DISEKOLAH DASAR UMUM 036/II SARANA JAYA - Putri, Nessa Alfira; Nabilla, Natasya; Andriani, Opi (Program Studi Pendidikan Vokasi Seni Kuliner, 2023)
This research aims to find out how regular teachers and students accept the presence of children with special needs, as well as how regular teachers and students respond to the physical presence of children with special needs in the 36 Sarana Jaya state elementary schools. This research approach is a qualitative approach with a descriptive type. This research was conducted on teachers and regular students regarding admissions (children with special needs) to class V at 36 Sarana Jaya elementary schools. The results of the research show that teachers and regular students at the 36 public primary schools in Sarana Jaya well accept the presence of children with special needs, with the presence of children with special needs the teachers do not differentiate between regular students and students with special needs at the school. Class teachers and special teachers have provided learning services/guidance, behaved in a good manner which is equivalent to how teachers provide study guidance and behave to regular students. So it can be concluded that in state elementary schools 36 jaya facilities the teachers in these schools do not discriminate against students with special needs and do not differentiate between the backgrounds between regular students and students with special needs as well as regular students who do not choose to make friends, which means teachers and Regular students at the school accept and behave well towards students with special needs physically like normal students.